Analytic geometry - Ochoa [and five others]; Amaya;Bandoy;Fainsan;Hisole;Sirug (Cavite : MRTTC Publication, 2004)
This book is intended to serve the dual-purpose of wordbook and textbook to students who are taking an Analytic Geometry subject. This is also an essential reference and a great tool for the teachers handling this subject in developing the innate mathematical skill of the students.
Chapter 1. Fundamental Concepts -- Chapter 2. Straight Lines -- Chapter 3. Algebraic Curves and Equations -- Chapter 4. Circles -- Chapter 5. Parabola -- Chapter 6. Ellipse -- Chapter 7. Hyperbola -- Chapter 8. Translation and Rotation -- Chapter 9. Polar Coordinates -- Chapter 10. Plane Geometry -- Chapter 11. Volumes of Common Solids.
Keywords: GEOMETRY -- MATHEMATICS